Drug Design and Aesthetic Obsolescence Pharmacologies for a Reformulated Concept of Virtual Reality - Santos, A.; Paquete, Hugo (Technoculture: an online journal of technology in society, Volume 12, 2022)
We propose an anthropological and technocultural analysis that follows the changeability of the tangibility of this subject, using David Le Breton in Farewell to the Body (2003). The urban- corporeal technoscientific imaginary is explored in complete decay, precariousness and imperfection, in which ‘Post-flesh’ Kroker (1994) and ‘Interzone’ (ibid) bodies. resting biomechanical objects maintain multiple connections in an expanding world in the third millennium. We explore the concepts of obsolescence and accident presented by William Kurtz at the Association for Strategic Accidents of 1990. We present in parallel ideas of “drug design” biochemical pharmacologies that allow new perception schemes that deal with ideas about virtual reality. As will be demonstrated in the course of the argument, there is a direct relationship between the expansion of VR technology immersion systems treated as virology and infection on the human senses, which generate the side effect of the immobilised body that is the result of a consensual hallucination (ibid) and desires to escape the body.